Destino corporal y rituales fúnebres: preferencias en la vejez - Mazzetti Latini, Carolina (El Colegio de México, 2022)
The article shows the funeral ritual preferences of elderly people in the city of Córdoba, Argentina. In line with the transformations in funeral rituals, the decision about the fate of the body fluctuates between personal autonomy, negotiation with the social environment and delegating matters to the family. In fact, a change of era has been identified in the validity of certain rites, as well as the use of creative practices, whose ritualization is assumed as a form of mediation to connect with life and death. The findings are part of a study on social imaginaries about death in old age, based on a qualitative analysis from an interpretative biographical framework.